ONECUT2 is a driver of neuroendocrine prostate cancer - Haiyang Guo (Nature Portfolio, 2019)
Neuroendocrine prostate cancer (NEPC) is characterized by loss of androgen receptor (AR) signaling during neuroendocrine transdifferentiation, resulting in resistance to AR-targeted therapy. Here they report ONECUT2 to drive NEPC tumorigenesis via regulation of hypoxia signaling and tumor hypoxia, and find hypoxia directed therapy to be effective in NEPC.